al-Ibrîz Menyajikan Tafsir Dengan Bahasa Mudah - Afif (LP2M Universitas PTIQ Jakarta, 2017)
This article talks about the interpretation of al-Ibrîz by Bisri Mustofa written in Javanese. The regional interpretation was written with the aim of being able to add to the khidmah of the author and the good deeds he did for Muslims, especially Javanese-speaking Muslims. In addition to being presented with mild, easy to digest, this interpretation provides concrete examples that occur in society, so that their contextuality is expressed through several concrete examples. Interpretation of al-Ibrîz is categorized as a normal interpretation, considering its descriptions which are mostly global in nature, although in some places a number of interpretations are found that are quite long.